2023
DOI: 10.1038/s41598-023-30696-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of scarcity promotion and cause-related events in impulse purchase in the agricultural product live stream

Abstract: Harvest agricultural products are perishable. If they cannot be sold, there will be serious grain loss and food waste. It is an important issue related to human sustainable development and urgent to address. As the most popular way of shopping, live shopping has achieved remarkable achievements, while the existing research is relatively silent on how to promote the sales of agricultural products in the context of live streams. Based on S–O–R theory and dual-system theory, three studies investigated the intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
1
1
0
Order By: Relevance
“…The findings for H4 were consistent with Study 1 and previous research, indicating that scarcity promotions, such as flash sales and time-limited delivery, trigger positive affect among Gen-Zers, leading to impulse purchases (Harikrishnan et al , 2022; Li et al , 2023; Marjerison et al , 2022; Martaleni et al , 2022). This underscores the effectiveness of scarcity-based marketing strategies for this demographic.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The findings for H4 were consistent with Study 1 and previous research, indicating that scarcity promotions, such as flash sales and time-limited delivery, trigger positive affect among Gen-Zers, leading to impulse purchases (Harikrishnan et al , 2022; Li et al , 2023; Marjerison et al , 2022; Martaleni et al , 2022). This underscores the effectiveness of scarcity-based marketing strategies for this demographic.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, scarcity strategies such as flash sales with timers have been shown to be essential for Gen-Z impulsive purchases (Marjerison et al, 2022). Previous research has found a positive relationship between scarcity and positive emotions such as excitement and arousal (Li et al, 2023). According to Wu et al (2021), limited quantity and time scarcity trigger a strong positive effect on consumers.…”
Section: Figure 2 Hypothesized Modelmentioning
confidence: 99%
“…Liu et al, 2018). One of the most important reasons is that the way of harvesting agricultural products for the consumers is obstructed, so it is urgent to alleviate the sales dilemma of agricultural products as well as food waste (X. Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%